Pengaruh Kecerdasan Intelektual dan Keterampilan Kerja terhadap Disiplin Kerja Karyawan PT. Primajaya Multi Technology Medan - David David; Thomas Sumarsan Goh; Chon Cho Reynols Manday; Syawaluddin Syawaluddin (Universitas Batanghari, 2022)
PT. Primajaya Multi Technology is a company that was founded in 2006 in the city of Medan with an orientation towards IT products which is equipped with more than 13 years of experience in this field. The research population that will be used in the study is all employees who work at the company as many as 62 employees. With a population of only 62 people, the sample collection technique used a saturated sample.Simultaneously there is a significant influence between the variables of intellectual intelligence and work skills on the work discipline of PT. Primajaya Multi Technology Medan. While partially found intellectual intelligence variables have a significant effect on the work discipline of employees of PT. Primajaya Multi Technology Medan. Partially it was found that the work skills variable had a significant effect on the work discipline of PT. Primajaya Multi Technology Medan. The results of this study indicate that the intellectual intelligence variable has more influence than work skills on the work discipline of PT. Primajaya Multi Technology Medan.